The Role of Language in Shaping Cultural Identity: An Analysis of Goyo: Ang Batang Heneral - Merry Luz, Molina; Meisur, Meisur; Rizky, Putri; Ayunda, Rizka (Pancasila International Journal of Applied Social Science, 2025)
This study explores the significance of language in creating cultural identity through an analysis of the recently-published Filipino classic Goyo: Ang Batang Heneral (2018), which shows General Gregorio del Pilar's actions during the Philippine-American War. In postcolonial contexts, language is a powerful tool for voicing dissent, negotiating power, and regaining cultural identities. The film's portrayal of language reflects the past battles of the Filipino people and serves as a symbol of resistance to colonial rule and national identity. Using Erving Goffman's book The Showing of Self in Everyday Life as a guide, this study explores communications as a performative strategy employed by characters to validate their sense of self in the socio-historical context of the Philippine Revolution. The study examines how Goyo's switch between Spanish and Filipino emphasizes resistance. This is self-determination, and cultural assertion throughout the war by fusing postcolonial theory, Bourdieu's idea of linguistic as a representation of power, and Critical Discourse Analysis (CDA). This study also highlights how language serves as a means of cultural resistance in Filipino cinema, as linguistic decisions influence identity and pride in the country. By focusing on the relationship between language and individual identity in Goyo, the study enhances the role of language in resisting colonial structures. Although earlier research has addressed linguistic changes in historical films, much is known about how these choices impact Filipino audiences today including their perceptions of their nation. Through new perspectives on language as well as perspectives about how language in Goyo impacts contemporary views of Filipino identity on resistance to culture, this study aims to bridge this divide.